RC beam strengthening using hinge and anchorage approach - Mugahed Amran, Y. H.; El-Zeadani, Mohamed; M. R., Raizal Saifulnaz; Alyousef, Rayed; Alabduljabbar, Hisham; Alrshoudi, Fahed; Alaskar, Abdulaziz (Elsevier, 2020)
Retrofitting of existing structures using adhesively bonded plates has been a major growth area in civil engineering and has gained well-deserved popularity over the past few years. This strengthening technique is in line with sustainable practices in construction and can be used to preserve eminent structures of historical or cultural values. This study aims to present an ideal design model for strengthening reinforced concrete elements using the hinge and anchorage design philosophies for retrofitting and plating existing structures. This includes a check on the intermediate crack (IC), critical diagonal crack (CDC), and plate end (PE) debonding mechanisms. The results of a theoretical model for an FRP plated reinforced concrete beam element were presented, and the findings showed that plating increased the shear at the datum point to cause a diagonal crack by 46.7%. The increase in moment capacity due to plating the hogging region was 64.3% while allowing for 30% moment redistribution from the sagging region to the hogging region. The accompanying increase in uniformly distributed load due to 30% moment redistribution was 42.8%. The results of the theoretical model were compared with previous design models for IC debonding to which it has been shown that following the anchorage approach, a higher strain in the plate may be allowed as compared to the hinge approach. In addition to the theoretical model presented, analysis on an FRP plated RC beam and slab were also presented to show the effect of different plate widths on the moment capacity and PE moment capacity.